Trauma, Psychopathic Traits, and Resilience in Female Post-Prison Reentry Outcomes - Helfgott, Jacqueline B. (Criminology, criminal justice, law & society, 2023)
A growing body of research has examined female psychopathy, yet gaps remain. Recent research has explored links between early trauma, psychopathic traits, and behavioral outcomes. Utilizing data collected as part of the evaluation of the Seattle Women’s Reentry (SWR) Initiative, this study investigates the relationship between early trauma and psychopathic traits in female post-prison reentry outcomes. The role of psychopathic traits as a protective resilience factor that moderates early trauma for women leaving prison and reentering the community is explored. Background information, survey data, and Psychopathy Checklist-Revised (PCL-R) scores are analyzed in relation to recidivism three-years post release for 85 women released from the Washington Corrections Center for Women (WCCW) in Washington State. Results indicated that the majority of the women in the study have early trauma backgrounds, PCL-R scores predict recidivism while trauma did not, and PCL-R scores did not moderate the relationship between trauma and recidivism. Results also found that PCL-R scores were associated with higher levels of self-esteem. Findings are consistent with prior research showing a link between psychopathic traits and recidivism but do not offer support for psychopathic traits as a moderating resilience protective factor between trauma and recidivism.